Augmenting Water Supply for Home Irrigation (Poster Session) - Popkin, Barney P. (Arizona-Nevada Academy of Science, 1979)
From the Proceedings of the 1979 Meetings of the Arizona Section - American Water Resources Assn. and the Hydrology Section - Arizona - Nevada Academy of Science - April 13,1979, Tempe, Arizona === Low rainfall and humidity, and high evapotranspiration, make irrigation necessary for domestic plant growth in the American Southwest. Irrigation supplies are limited. A large percentage of potable water used in Southwestern homes is used for home irrigation. Another large percentage Is returned to sewers. Water and sewer fees are increasing because of rapid urban expansion and increased water-quality standards. As fees increase, supplemental home irrigation sources become attractive and are sought. Major supplemental water sources are grey water, harvested runoff, and roof runoff. The amount of grey water depends on family size and habits. The amount of harvested runoff depends on land size and slope, soil's and material's properties, and rainfall. The amount of roof runoff depends on roof size and geometry, and rainfall. The quality of these sources is generally suitable for home irrigation. Engineering systems are required to use supplemental home irrigation water. The most preferred systems will have low capital expenditure and low energy requirements. A large and significant reduction in municipal costs and services is possible if supplemental home irrigation water is developed. Small-scale analysis indicates that costs are favorable for supplemental irrigation systems. A suggested research program emphasizes field trials and demonstrations which test design, operation, maintenance, and economics, as well as public and institutional acceptance.